D.H. Lawrence, the Mining Community, and the Paternal Home - Marie-Geraldine Rademacher (Études Lawrenciennes)
Over the years, the notion of “home” has been commonly associated with the image of a caring mother, devoted to providing an “ideal home” for her children. In that context, the “home” is a place where children can thrive under their parents’ watch and protection. However, in Sons and Lovers, the mother’s high-handed attitude towards the father and by extension towards the mining community, results in creating a disharmonious household and estranging the children from their father. Family tensions and the mother’s stifling love have urged the children to seek escape from the family nest. In D.H. Lawrence’s works, the notion of “home” is not necessarily connected with the maternal but rather with the paternal. For instance, in the poem “Nostalgia,” the speaker realizes that following the death of his father, “the place is no longer ours.” Then, in his late essay “Return to Bestwood,” talking about the coal miners, Lawrence confesses that “It is they who are, in some peculiar way, ‘home’ to me […] the miners at home are men very much like me, and I am very much like them […]" (155). This statement establishes a connection between the writer’s own father (Arthur Lawrence), the mining community and Lawrence’s idea of home. For D.H. Lawrence, home is more than just a space or a place, it has more to do with the idea of a shared intimacy and the sentiment of belonging to a community. His late writings are tinged with nostalgia for a distant past, for a time when the collective was prioritized over the individual, before homeliness was superseded by homelessness; homelessness which according to Karl Marx, finds its root in capitalism and social inequalities.